IMPLEMENTASI EVALUASI NON TES PADA PEMBELAJARAN AKHLAK DI SMP 2 MUHAMMADIYAH SURAKARTA - Asma Nurul Azizah; Balqis Tania Prayoga; Isna Nur Mandhasihanni; Vania Siska Damayanti; Nurul Latifatul Inayati (CV. ADIBA AISHA AMIRA, 2025)
This study aims to examine the implementation of non-test evaluation in moral learning at SMP Muhammadiyah 2 Surakarta. The research method used is a qualitative approach with data collection techniques through observation, interviews with one of the teachers, and library research. The results showed that the implementation of non-test evaluations, such as observations of worship practices, congregational prayers, muroja’ah, and observations of student behavior, provided a comprehensive picture of students' moral development. Moral learning at SMP Muhammadiyah 2 Surakarta has also generally been implemented well, and the learning outcomes also show satisfactory achievements. However, there are several aspects in its implementation that need to be improved to improve the quality of the learning program such as the challenge of integrating moral values as a whole into students' daily behavior. This research recommends improving teacher competence, developing a comprehensive assessment rubric, and allocating adequate time and resources to support the successful implementation of non-test evaluation in moral learning. Similar research has also been conducted, for example by Ramadhan et al., (2024) which discusses non-test learning evaluation in morals subjects at SMP MUH 1 Karanganyar, as well as in the journal Natasya et al., (2024) which examines the implementation of non-test evaluation through microteaching practices in Aqidah Akhlak courses at UMS. Whereas in this study, it is focused on what and how the implementation of non-test evaluation in moral learning at SMP Muhammadiyah 2 Surakarta which has not been discussed in these studies.